2014
DOI: 10.1128/mbio.00870-14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Two-Component Systems in Group B Streptococcus Shows That RgfAC and the Novel FspSR Modulate Virulence and Bacterial Fitness

Abstract: Group B Streptococcus (GBS), in the transition from commensal organisms to pathogens, will encounter diverse host environments and, thus, require coordinated control of the transcriptional responses to these changes. This work was aimed at better understanding the role of two-component signal transduction systems (TCS) in GBS pathophysiology through a systematic screening procedure. We first performed a complete inventory and sensory mechanism classification of all putative GBS TCS by genomic analysis. Five TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 47 publications
3
74
0
Order By: Relevance
“…Control of these genes suggests that RgfC regulation of gene expression is altered in the absence of a functional RgfA and that sensor kinase has a broader role in GBS virulence than previously appreciated. Support for this observation also is provided by the recent findings of Faralla et al (21). The authors reported that the deletion of RgfC in the GBS serotype V strain CJB11, which encodes a functional RgfA, resulted in increased mortality of mice without significant differences in bacterial dissemination (21).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Control of these genes suggests that RgfC regulation of gene expression is altered in the absence of a functional RgfA and that sensor kinase has a broader role in GBS virulence than previously appreciated. Support for this observation also is provided by the recent findings of Faralla et al (21). The authors reported that the deletion of RgfC in the GBS serotype V strain CJB11, which encodes a functional RgfA, resulted in increased mortality of mice without significant differences in bacterial dissemination (21).…”
Section: Discussionsupporting
confidence: 68%
“…The same point mutation in rgfA also was identified in other GBS clinical strains, such as H36B (9) (Fig. 1B) and 61 other GBS strains (21). To determine if RgfC had a significant role in gene regulation and virulence of GBS in strains lacking a functional RgfA, we constructed a strain deficient in rgfC expression from the wild-type (WT) strain A909.…”
Section: Gbs Deficient In Rgfc Expression Exhibit Increased Virulencementioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative RT-PCR Analysis-RNA extracts were prepared as described (24). Bacteria were harvested at two time points, at A 600 ϭ 0.4 (log phase) and A 600 ϭ 1.7 (early stationary phase).…”
Section: Methodsmentioning
confidence: 99%